2019
DOI: 10.1186/s11689-019-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic spectral power as a marker of cortical function and disease severity in girls with Rett syndrome

Abstract: Background Rett syndrome is a neurodevelopmental disorder caused by a mutation in the X-linked MECP2 gene. Individuals with Rett syndrome typically develop normally until around 18 months of age before undergoing a developmental regression, and the disorder can lead to cognitive, motor, sensory, and autonomic dysfunction. Understanding the mechanism of developmental regression represents a unique challenge when viewed through a neuroscience lens. Are circuits that were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 43 publications
7
64
0
Order By: Relevance
“…In both regions, changes in delta or alpha power was not seen in the MUT animals at the younger age. Elevation of delta power in MUT animals is consistent with similar observations in people with RTT ( Ammanuel et al, 2015 ; Roche et al, 2019 ), with correlation to clinical severity in people with RTT. Thus, increased delta power has the potential to serve as a translational neurophysiological biomarker ( Roche et al, 2019 ), but formal additional characterization and validation is needed.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In both regions, changes in delta or alpha power was not seen in the MUT animals at the younger age. Elevation of delta power in MUT animals is consistent with similar observations in people with RTT ( Ammanuel et al, 2015 ; Roche et al, 2019 ), with correlation to clinical severity in people with RTT. Thus, increased delta power has the potential to serve as a translational neurophysiological biomarker ( Roche et al, 2019 ), but formal additional characterization and validation is needed.…”
Section: Discussionsupporting
confidence: 86%
“…Previous work in people with RTT used 1/f slope of the power spectrum between 2 and 24 Hz (log-log transformed) to investigate excitatory/inhibitory imbalance and the effect of neural noise ( Roche et al, 2019 ; Voytek et al, 2015 ), and found that people with RTT have a significantly more negative slope compared to typically developing controls. We conducted a similar analysis of the 1/f slope from the experimental animals ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3), these findings suggest that EEG power may serve as a marker for disease severity. In support of this, reduced EEG power has also been found to correlate with the severity of phenotype in Rett syndrome (Roche et al, 2019). Furthermore, in neonatal seizures and hypoxic ischemic encephalopathy, epileptic episodes during suppressed background EEG were correlated with more severe epilepsy (Korotchikova et al, 2011;Rowe et al, 1985).…”
Section: Reduced Eeg Power At the Worsening Stage Of Dravetmentioning
confidence: 68%